Dynamic passive sampling of hydrophobic organic compounds in surface seawater along the South Atlantic Ocean east-to-west transect and across the Black Sea - Sobotka, Jaromír; Lammel, Gerhard; Slobodník, Jaroslav; Schink, Anne; Prokeš, Roman; Vrana, Branislav (Marine pollution bulletin, 2021)
Mapping of hydrophobic organic compounds (HOCs) in surface seawater on an east-to-west transect of the South Atlantic Ocean (SAO) and across the Black Sea (BS) in 2016 was performed by a dynamic passive sampling device containing silicone-based passive samplers. In SAO as well as in BS the measurements confirmed freely dissolved concentrations of polychlorinated biphenyls, DDT and its metabolites, chlorobenzenes, cyclodiene pesticides, and brominated flame retardants in the range of units to low hundreds of pg per litre. The findings indicate that the spatial distribution of HOCs and emerging pollutants in the SAO and the BS is influenced by riverine inputs, ocean currents and atmospheric deposition from continental plumes. Observed concentration gradients indicate that eastern SAO receives DDT from sources in South Africa, whereas the emissions of endosulfan originate in South America. Elevated HOC concentrations in the northwestern BS are related to their discharge by rivers from the European continent.
Keywords: Seawater; South America; Polychlorinated Biphenyls; Halogenated Diphenyl Ethers; halogenované difenylethery; monitorování životního prostředí; South Africa; polychlorované bifenyly; Atlantský oceán; Black Sea; Polychlorinated biphenyls; Contamination; Jihoafrická republika; Polybrominated diphenyl ethers; Brominated flame retardants; Free dissolved concentration; Atlantic Ocean; Marine pollution; Organochlorine pesticides; Persistent organic pollutants; Environmental Monitoring; Silicone; Jižní Amerika; Pesticides; Passive sampling; mořská voda; pesticidy; Černé moře